Impacts of anions on activated persulfate oxidation of Fe(II) - Rich potassium doped magnetic biochar. (January 2023) - Luo, Jiayi; Yi, Yunqiang; Zhou, Long; Fang, Zhanqiang
Abstract: The potassium-doped magnetic biochar (KMBC) preparation was inevitably introduced the different anions in the process of modifying magnetic biochar (MBC) with different potassium salts, but the effect and mechanism of different anion on KMBC activation properties has not been reported. Therefore, in this paper, five different KMBCs were prepared using several common potassium salts under the same dosage of K + and Fe 2+, and then was added in the presence of persulfate (PS) for the removal of metronidazole (MNZ). The removal rate of metronidazole was ordered as KMBCK2SO4 (98.40%) > KMBCKNO3 (76.84%) > KMBCKCl (20.79%) > KMBCK2CO3 (19.02%) > KMBCK2C2O4 (14.23%). However, the semi-quantitative of Fe(II) experiments results confirmed that the effectively increase of Fe(II) content by potassium salts modification played the dominant role in improvement of KMBC activation performance. The Fe(II) content of KMBC were ordered as KMBCK2CO3  > KMBCK2SO4  > KMBCKNO3  > KMBCKCl  > KMBCK2C2O4, with the Fe(II) content of KMBC of 36.74, 17.70, 8.79, 5.24 and 4.85 mg/g, respectively. The indicated that the introduction of different anions would lead to different optimal Fe(Ⅱ) content in KMBC modified with different potassium salts, which was most directly reflected in 1 O2 content in different KMBC/PS systems, and account for the difference in MNZ degradation efficiency. Meanwhile, when the Fe(II) content in KMBC reached the range of 13.7–28.8 mg/g, KMBC had the better performance of activating PS. Graphical abstract: Image 1 Highlights: Five different KMBCs were prepared using several common potassium salts. The introduction of different anions would lead to different optimal Fe(Ⅱ) content in KMBC modified with different potassium salts. The content of Fe(II) in KMBC can be enhanced according to introduced the different anions. When the content of Fe(II) reached the range of 13.7 to 28.8 mg/g, KMBC had the better performance of activating PS.